Contemporary issues in severe aortic stenosis: review of current and future strategies from the Contemporary Outcomes after Surgery and Medical Treatment in Patients with Severe Aortic Stenosis registry. Issue 11 (29th February 2020) - Taniguchi, Tomohiko; Morimoto, Takeshi; Takeji, Yasuaki; Kato, Takao; Kimura, Takeshi
Abstract : Contemporary Outcomes after Surgery and Medical Treatment in Patients with Severe Aortic Stenosis (CURRENT AS) registry was a large Japanese multicentre retrospective registry of consecutive patients with severe aortic stenosis (AS) before introduction of transcatheter aortic valve implantation. We sought to overview the data from the CURRENT AS registry to discuss the three major contemporary issues related to clinical practice in patients with severe AS: (1) under-referral/underuse of surgical aortic valve replacement (SAVR) in symptomatic patients with severe AS, (2) management of asymptomatic patients with severe AS and (3) management of patients with low-gradient severe aortic stenosis (LG-AS). First, despite the dismal prognosis of symptomatic patients with severe AS, SAVR, including those performed during follow-up, was reported to be underused. In the CURRENT AS registry, overall 53% of symptomatic patients underwent aortic valve replacement (AVR) during follow-up. Second, we reported that compared with conservative strategy, initial AVR strategy was associated with lower risk of all-cause death and heart failure hospitalisation in asymptomatic patients with severe AS. Although current recommendations for AVR are mainly dependent on the patient symptoms, some patients may not complain of any symptom because of their sedentary lifestyle. We also reported several important objective factors associated with worse clinical outcomes in asymptomatic patients with severe AS for risk stratification. Finally, initial AVR strategy was associated with better long-term clinical outcomes than conservative strategy in both patients with high-gradient AS and patients with LG-AS. The favourable effect of initial AVR strategy was also seen in patients with LG-AS with left ventricular ejection fraction of ≥50%.